New Prediction Models of Functional Outcome in Acute Intracerebral Hemorrhage: The dICH Score and uICH Score - Yang, Wen-Song; Shen, Yi-Qing; Wei, Xiao; Zhao, Li-Bo; Liu, Qing-Jun; Xie, Xiong-Fei; Zhang, Zhi-Wei; Deng, Lan; Lv, Xin-Ni; Zhang, Shu-Qiang; Li, Xin-Hui; Li, Qi; et al. (Frontiers in Neurology, 2021)
Objectives: The original intracerebral hemorrhage (oICH) score is the severity score most commonly used in clinical intracerebral hemorrhage (ICH) research, but may be influenced by hematoma expansion or intraventricular hemorrhage (IVH) growth in acute ICH. Here, we aimed develop new clinical scores to improve the prediction of functional outcome in patients with ICH. Methods: Patients admitted to the First Affiliated Hospital of Chongqing Medical University with primary ICH were prospectively enrolled in this study. Hematoma volume was measured using a semiautomated, computer-assisted technique. The dynamic ICH (dICH) score were developed by incorporating hematoma expansion and IVH growth into the oICH score. The ultra-early ICH (uICH) score were developed by adding the independent noncontrast CT markers to the oICH score. Receiver operating characteristic curve analysis was used to compare performance among the oICH score, dICH score, and uICH score. Results: This study included 76 patients (23.3%) with hematoma expansion and 61 patients (18.7%) with IVH growth. Of 31 patients with two or more noncontrast computed tomography markers, 61.3% died and 96.8% had poor outcomes at 90 days. After adjustment for potential confounding variables, we found that age, baseline Glasgow Coma Scale score, presence of IVH on initial CT, baseline ICH volume, infratentorial hemorrhage, hematoma expansion, IVH growth, blend sign, black hole sign, and island sign could independently predict poor outcomes in multivariate analysis. In comparison with the oICH score, the dICH score and uICH score exhibited better performance in prediction of poor functional outcomes. Conclusions: The dICH score and uICH score were useful clinical assessment tools that could be used for risk stratification concerning functional outcomes and provide guidance in clinical decision-making in acute ICH.